Teaching performance of specialized educational assistance against the use of computational technologies in multifunctional resource rooms: a case study (Research, Society and Development, 2022)
Objective: to investigate public educational policies (PPE) on the teaching performance of Specialized Educational Assistance (AEE) in the face of the use of computational technological resources (RTC) in Multifunctional Resource Rooms (SRM), based on Normative Frameworks, documentation and scientific research that present information of this nature. Methodology: this is qualitative research through the Case Study method, where the document analysis technique was used through the stages of search, extraction, tabulation and data analysis. Results: in view of the data extracted from the studies, it was possible to present a summary of what public policies cite about the use of RTC in the teaching and learning process in SRM in AEE. Thus, listing characteristics of training and attributions given to AEE teachers in contrast to their training. Conclusion: through this study it was possible to show that the AEE teacher training implies a multicategorized training and full of challenges, because in addition to dealing with the existing diversity among the students who are the target audience of the AEE, the knowledge of the RTC in the SRM becomes indispensable so that improvements in the teaching process in the AEE.